2021
DOI: 10.1039/d0mh01710h
|View full text |Cite
|
Sign up to set email alerts
|

Porous flexible frameworks: origins of flexibility and applications

Abstract: All major classes of porous crystalline frameworks including zeolites, metal–organic frameworks, covalent organic frameworks and hydrogen-bonded organic frameworks exhibit structural flexibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 182 publications
0
60
0
Order By: Relevance
“… 10 Flexible MOFs undergo temperature-influenced pressure-induced reversible phase transitions between an activated, dense phase with reduced accessible porosity and a gas-dosed, open phase with greater accessible porosity. 11–15 This behavior may manifest as a “step” in gas adsorption at the phase transition pressure ( Fig. 1 , blue curve).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Flexible MOFs undergo temperature-influenced pressure-induced reversible phase transitions between an activated, dense phase with reduced accessible porosity and a gas-dosed, open phase with greater accessible porosity. 11–15 This behavior may manifest as a “step” in gas adsorption at the phase transition pressure ( Fig. 1 , blue curve).…”
Section: Introductionmentioning
confidence: 99%
“…A very exciting and important development in MOFs is the generation of flexible solids, also known as soft porous crystals (SPCs) . In these materials the structure can be altered in a reversible manner under specific external stimuli (e.g., host–guest interactions, temperature, and pressure), without bond breaking, while maintaining crystallinity. These kinds of MOFs are currently representing a key direction in state-of-the-art MOF research, as control of this dynamic behavior opens novel pathways toward the development of adaptive and/or responsive materials for advanced applications, including selective gas storage, capture and separation, and fluorescence-based sensing, among others. However, a limited number of flexible MOFs exist and are mainly based on first row transition metals and main group elements, where the observed dynamic behavior is associated with either ligand flexibility, a hinge-like motion of the coordinating groups, or network displacement in the case of interpenetrated MOFs. …”
Section: Introductionmentioning
confidence: 99%
“…The structure of the crystalline material was established by single crystal structure analysis and the framework was found to possess sufficient Brønsted acidity to promote epoxide ring-openings and a Diels–Alder reaction . The study was a preliminary one but indicated that even F-1a , which does not possess significant pores, was able to absorb substrates by rearrangement of the matrix via a process called stimuli induced breathing . Still, it seemed self-evident that the porosity of a crystalline framework should be an important factor in making a heterogeneous catalyst much more efficient.…”
Section: Introductionmentioning
confidence: 99%